A REVIEW ON RECENT AVAILABLE POSITIONING TECHNOLOGIES AND ITS ADVANCEMENT - Chai, Nee Ping; Wan Zainal Abidin, Wan Azlan; Wan Ibrahim, Wan Hashim; Anak Hong Ping, Kismet (Malaysian Journal of Science, 2015)
This paper reviews and compares the available positioning technology for location based application such as the Intelligent Transport System (ITS) and personal vehicle positioning. With the rapid growing trend of worldwide vehicle ownership, issues such as traffic congestion, environmental pollution, energy consumption and road accident cases are increasing. Intelligent Transportation System (ITS) which depends on location and positioning has been identified as one of the advocated key to resolve the issues. Global Positioning System (GPS) is one of the most promising ubiquitous positioning technologies accepted worldwide for ITS application. It is discerned that GPS alone in ITS application is not adequate since GPS faced Non-Line-of-Sight (NLOS) and multipath effect. New technology integrated is needed to overcome the drawback of the current system for continuous positioning; particularly important for ITS application to be fully functional. This is the significant motivation for tremendous research works had been carried out to improve the performance of positioning. In this paper, advantages and disadvantages of the recent available positioning technologies being used in the implementation of ITS such as satellite-based positioning, network-based positioning and location integration of several positioning technologies is found to be able to improve accuracy, reliability, availability and applicability of the ITS. ABSTRAK Kertas kerja ini membandingkan teknologi penentududukan untuk aplikasi berasaskan lokasi seperti Intelligent Transportation System (ITS) serta penentududukan bagi kenderaan persendirian. Dengan trend pemilikan kenderaan yang meningkat di seluruh dunia, isu-isu seperti kesesakan lalu lintas, pencemaran alam sekitar, penggunaan tenaga dan kes-kes kemalangan jalan raya semakin serius. Intelligent Transportation System (ITS) yang bergantung kepada maklumat lokasi dan penentududukan telah dikenal pasti sebagai salah satu kaedah yang dapat membantu menyelesaikan isu-isu tersebut. Global Positioning System (GPS) adalah salah satu daripada teknologi penentududukan yang diterimapakai di seluruh dunia bagi aplikasi ITS. Namun begitu, teknologi GPS sahaja adalah tidak memadai kerana masalah Non-Line- of- Sight (NLOS) dan kesan berbilang arah (multipath). Bagi mengatasi kelemahan sistem GPS dan untuk membolehkan ITS berfungsi sepenuhnya, penentududukan yang berterusan adalah penting tanpa masalah NLOS dan kesan berbilang arah. Masalah ini telah menjadi satu motivasi kepada penyelidikan bagi menambahbaik prestasi sistem penentududukan. Kebaikan dan keburukan teknologi baru penentududukan yang ada digunakan dalam pelaksanaan ITS seperti penentududukan berasaskan satelit, penentududukan berasaskan rangkaian dan Integrasi lokasi beberapa teknologi kedudukan didapati dapat meningkatkan ketepatan, kebolehpercayaan, ketersediaan dan kebolehgunaan aplikasi ITS . Keywords: Positioning technologies, GPS, NLOS, multipath effect, integration